ANALISIS SWOT PADA PENGEMBANGAN FINTECH SYARIAH DALAM EKOSISTEM EKONOMI DIGITAL - Syafitri, Wulan Rindyana; Trisena, Puja (Taksasila Edukasi Insani, 2025)
The rapid digital transformation has reshaped the landscape of the financial services sector, including the growth of Islamic finance through the emergence of Sharia-compliant financial technology (fintech) platforms. This study aims to analyze the strategic position of Islamic fintech in Indonesia using a SWOT analysis framework to identify its strengths, weaknesses, opportunities, and threats within the digital economy ecosystem. Employing a descriptive qualitative approach, this research collects secondary data from various relevant literature and policy documents. The analysis reveals that the primary strength of Islamic fintech lies in its compliance with Sharia principles and its established institutional legitimacy. Its weaknesses include the low level of Islamic financial literacy and a shortage of human resources with dual competencies in both technology and Islamic jurisprudence. Opportunities include strong national policy support for the Islamic economy, a large Muslim market share, and a growing trend toward digitalization. However, Islamic fintech also faces serious threats such as the dominance of conventional fintech entities, data security risks, and suboptimal public trust. These findings highlight the urgent need for integrative strengthening strategies through technological development, improved Islamic financial literacy, and comprehensive policy support, enabling Islamic fintech to play a significant role in promoting inclusive, fair, and sustainable financial development in Indonesia.Keywords : digital economy, financial inclusion, financial literacy, islamic fintech, SWOT analysis